Cleaning after solar panels: applying a circular outlook to clean energy research. Issue 1 (2nd January 2022) - Duran, A. Serasu; Atasu, Atalay; Van Wassenhove, Luk N.
Abstract : In this paper, we study the link between renewable technology adoption and the resulting waste, drawing parallels from our experience with the WEEE Directive to suggest policy recommendations and highlight future research directions. Our ideas are driven by the observation that the sharp reduction in solar panel installation costs along with improvements in their energy conversion efficiency has driven a rapid growth in the adoption of this technology. We note a potential caveat to such rapid growth in adoption: existing installations being retired earlier than their projected 30-year lifetime. In this context, we build a model of the technology adoption and replacement behaviour of solar panel end-users. We conduct a numerical analysis to calculate the solar panel replacement incentives of US residential households, and project the resulting waste from residential panels. We find that annual new waste introduced into the market can exceed the volume of new installations within the next decade, which can more than double the levelized cost of energy for solar generation and jeopardise the cost competitiveness of this technology in the foreseeable future. These observations reflect the importance of a circular economy outlook in renewable energy system design and call for further research in this area.